Paulus er ikke død - han lugter bare grimt: Den aksiale værdiomkalfatrings betydning for tidlig Kristusreligion - Klostergaard Petersen, Anders (Religionsvidenskabeligt tidsskrift, 2019)
Through a discussion of Dostoevsky's depiction of the death of the staret in Brothers Karamazov, I discuss the olfactory channel of communication in religion with the aim in mind to tease apart the underlying ontology pertaining to different forms of religion. The focus is on impurity related to putrefaction in death. Contrary to the understanding represented by the ironic voice of the narrator in Brothers Karamazov, I explore the view holding the saintly person to undergo an olfactory transformation in death changing into a pleasurable aroma and thereby becoming an indexical token of celestial life. From Brothers Karamazov, I proceed to examine notions of divine presence and olfactory tokens in ancient Graeco-Roman culture. I use it as a historical foil to analyse Paul's total inversion of the motif in 2 Cor 2, 14-17 and 4, 7-12 in which he portrays himself and his Christ-message as an indexical putrefaction of Christ. Thus, the title of my essay: "Paul isn't dead, he just smells funny." Finally, I discuss the extent to which such an understanding is encompassed by Philippe Descola's notion of analogistic ontology.